A 'disappointing' leader: the postmaternalism of public feminist commentary on Julia Gillard. Issue 3 (3rd May 2016) - Bourgault du Coudray, Chantal
Abstract: Postfeminist media culture – or 'internet feminism' – readily enabled widespread feminist celebration of Julia Gillard's empowerment, defence of her rights to equality and critique of the sexism that dogged her. However, this paper examines such public feminist commentary for the ways in which it sidelined women's studies scholarship on the possible contributions of women's 'difference' to public life. This marginalization was in keeping with the culture of postmaternalism described by Julie Stephens, which entails a widespread disavowal of the maternal and themes of care or sociality, including within feminism. Nevertheless, consistent recourse to the word 'disappointing' to describe Gillard's performance – particularly by those on the left of the political spectrum – suggested a submerged desire for Gillard to do leadership differently, and with more 'care'. In the absence of a robust and recognizable vocabulary for publicly articulating the links between care, sociality, women and politics – a vocabulary which might conceivably have provided Gillard with a more supportive script to follow – the prevailing feminist commentary struggled to diagnose and enunciate the systemic issues that constrained her ability to alter the political culture in which she was embedded. Ultimately, this paper argues that a significant task for public feminism is to disseminate the language and logic that will enable subsequent women in politics to claim greater authority and expertise with regard to the performance and provision of sociality and care.